PENINGKATAN KAPASITAS PETANI MELALUI PENDAMPINGAN PENERAPAN PUPUK ORGANIK CAIR BERBASIS LIMBAH LOKAL - Yoyon Riono; Muhammad Arpah (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2026)
This community service activity was conducted in Pulau Palas Village, Indragiri Hilir Regency, with the aim of enhancing the capacity of horticultural farmers to utilize local organic waste as liquid organic fertilizer (LOF). The main problems faced by the partners included dependence on chemical fertilizers, limited farming capital, and the low utilization of organic waste. The implementation methods consisted of counseling sessions, hands-on training on the production of liquid organic fertilizer, and field assistance in the application of LOF to horticultural crops, involving 30 members of a farmers’ group. Data were collected through observation, interviews, documentation, and measurement of plant growth, and were analyzed using descriptive and thematic approaches. The results showed an improvement in farmers’ knowledge and skills in independently producing and applying liquid organic fertilizer. The application of LOF resulted in positive responses in plant growth and encouraged changes in farmers’ attitudes toward more environmentally friendly agricultural practices. This activity contributed to reducing farmers’ dependence on chemical fertilizers and supporting the sustainability of farming systems based on local resources.